Mereduksi Perilaku Konsumtif Siswa SMA Melalui Konseling Kelompok Teknik Self-Management - Handayani, Eka Sri; Haryadi, Rudi (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Consumptive behavior can be said to be the behavior of using every available item. Consumptive behavior is often carried out with the aim of fulfilling a need, whether primary or tertiary. Consumptive behavior is the behavior of buying goods excessively and irrationally without prioritizing needs. Consumptive behavior is often carried out with the aim of fulfilling a need, whether primary or tertiary. This research has short-term and long-term goals. The short-term objectives include: (1) to find out the description of consumer behavior at SMA Negeri 2 Banjarmasin, (2) To find out the picture of consumptive behavior before and after participating in individual counseling with self-management techniques for students at SMA Negeri 2 Banjarmasin, (3) To knowing that the consumer behavior of SMA Negeri 2 Banjarmsin students can be overcome through group counseling with self-management techniques. Meanwhile, the long-term goals are: (1) literature for guidance and counseling teachers in guiding high school students who have consumer behavior, (2) as reference material for further research, (3) theoretical development in the field of guidance and counseling. The type of research used is experimental research (non-parametric). Researchers use this experimental pattern to see the effects of treatment (group counseling with self-management techniques) on other variables (consumptive behavior). This research is a type of quasi-experimental design, using a one-group pre-test and post-test design. With this design, it is determined that there is no control group. With the one group pre-test and post-test design method, this means that the sample is given a test before and after receiving a certain treatment, so that the subject is subjected to two measurements.